Long-life performance of biogas systems for productive applications: The role of R&D and policy - Edmund Tumusiime; John B. Kirabira; Wilson B. Musinguzi (Energy Reports, 2019)
In order to achieve the transformations required to realize sustainable development, the use of modern renewable energy has to increasingly take primacy. Biogas technology is one of listed modern RETs but despite its early introduction in Uganda, its adoption rate remains very low amidst high technology failure and dis-adoption. To investigate this, a field-based assessment was conducted to evaluate performance of productive biogas installations with an aim of determining the root cause of this poor performance. It was found out that over 50% of productive biogas installations failed within two years after their commissioning due to logistical and technological challenges. Most installations could not sustain biogas production due to deprived quality of digester feed, and lack of local technical data to utilize alternatives during scarcity of the primary feedstock. Insufficient R&D in the biogas sector is suggested to be the lead cause of such poor performance. Therefore, novel policy strategies for promoting R&D have been proposed in this paper because for success of any productive biogas system, optimization of energy recovery through R&D must be at the forefront in order to drive system outputs to better economic gain.
Keywords: 330; Energy Policy; Optimization; Productive biogas; Research & Development; Sustainability